2015
DOI: 10.1016/j.jvs.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Nellix EndoVascular Aneurysm Sealing system experience in aneurysm sac sealing

Abstract: This first multicenter postmarket report of the Nellix device for infrarenal abdominal aortic aneurysm repair demonstrates satisfactory results during the initial learning phase of this new technology. The rate of aneurysm exclusion was high, and frequency of complications was low. More definitive conclusions on the value of this novel device await the results of the ongoing Nellix EVAS FORWARD Global Registry and the EVAS FORWARD investigational device exemption trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 33 publications
6
116
1
2
Order By: Relevance
“…Böckler and colleagues, in a recent multicentre case series analysis, reported type 1a, type 1b and type II endoleaks in a small number of patients [3]. Authors in the same publication documented the need for aneurysm-related interventions in 15 patients (9%) but there was an absence of any aneurysm ruptures or open surgical conversions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Böckler and colleagues, in a recent multicentre case series analysis, reported type 1a, type 1b and type II endoleaks in a small number of patients [3]. Authors in the same publication documented the need for aneurysm-related interventions in 15 patients (9%) but there was an absence of any aneurysm ruptures or open surgical conversions.…”
Section: Introductionmentioning
confidence: 99%
“…The Nellix® endoprosthesis (Endologix Inc, Irvine, California, USA) has been used to treat numerous patients with abdominal aortic aneurysms (AAA) [1][2][3]. The use of a sac-anchoring endograft such as the Nellix® has brought a change in the approach to aneurysm exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a novel technique, the endovascular aneurysm sealing (EVAS) technique, has emerged in an attempt to circumvent the afore-mentioned long-term deficiencies of EVAR, in particular migration and endoleak [3]. Even though EVAS applies the same procedural principle for the treatment of abdominal aortic aneurysms as EVAR, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Böckler et al 2 reported similar good results of EVAS in a multicenter experience, including some patients from SGVI. Mortality was zero out of 171 patients, technical success was 99%.…”
mentioning
confidence: 76%